PREDIKSI PASOKAN BAWANG MERAH MENDUKUNG DESAIN PENGEMBANGAN AGROINDUSTRI DI PROVINSI ACEH - Rizki Ardiansyah; Rachman Jaya; Yusriana Yusriana; Cut Hilda Rahmi (Jurnal Teknologi Industri Pertanian, 2021)
One of the focus of agricultural commodities development is shallot. It was contributed on national and regional inflation. Therefore, is not a national centra prodcution of shallot, Aceh Province has shallot centra productio, namely at Pidie, Aceh Tengah and Aceh Besar district. As we know that the main character agricultural product was seasonal, thus sholud be effectivally managed of its. The objectives of this research were to obtain prodcution shallot pattern and to design a agroindustrial model which suitable with shallot characteristic production. The technique used Auto Regresive Moving Average (ARIMA), the data is used time-series (monthly) for 6 month, whereas option design model and product used Analitical Hierarcy Process (AHP). The result of study show that a model of ARIMA (p,d,q) was (0,0,1) with mean square 20,682,669. Meanwhile, the prediction of production t+1=6,662 qiuntal. The option of model design was micro-agroindustrial with a weight (0,59), small-agroindustrial (025). Whereas the main product was pasta (0,41), shallot (0,26) and shallot-cuted (0,19) Key words: Agroindustrial, Shallot, ARIMA and AHP